PEMANFAATAN TEPUNG KETAN HITAM PADA PENGEMBANGAN PRODUK PANGAN LOKAL KLEPON KETAN HITAM (KLEPKETAM) - Dra. Rizqie Auliana, M.Kes, Amelia Oktavia Dewi (Prosiding Pendidikan Teknik Boga Busana, 2020)
This study aims to improve local food development through product innovation klepon with substitution of black glutinous flour by knowing the level of product composition development, acceptability in the community and testing of nutritional content. The type of research used is R&D(Research and Development) with the 4D development model (define, Design, Develop, Disseminate). The place and time of the study is the Food Laboratory of Food and Fashion Engineering Education Department, Faculty of Engineering, Yogyakarta State University, starting from February-April 2019. The test material is in the form of samples from each product, while the testing instruments are experimental forms, Validation forms I and II, panelist sensory, and preferred test forms during exhibitions with data analysis techniques. The results obtained from the research of this product are 1) The right recipe for KLEPKETAM products is the product of white glutinous flour klepon substituted with 50% black glutinous flour. 2) The value of the community’s acceptability of KLEPKETAM product is 3.8 with information that is very preferred, form these data indicating that the product is acceptable to the community. 3) Based on the proximate test results, the highest content is found in carbohydrate content with the results of 14.92gr/100gr and the lowest is the fat content of 2.74gr/100gr. 4) Based on %AKG fiber is 15% and the lowest is fat 4%. Keywords: Local food, Black Glutinous Flour, Development, Acceptability, Nutrition Test